Hubungan Pengetahuan Mengenai Tanda Perdarahan dengan Kunjungan Antenatal pada Ibu Hamil Trimester III - Ulty Desmarnita; Noviola Lolita; Sri Djuwitaningsih; Yuli Mulyanti (Jurnal Keperawatan, 2021)
Knowledge is an important factor for pregnant women to be able to adapt to physiological and psychological changes during pregnancy. Failure to adapt causes several health problems for pregnant women, one of which is bleeding. Bleeding events can be prevented by obediently carrying out antenatal visits. To determine the relationship between respondent’s characteristics and knowledge of signs of bleeding during pregnancy with antenatal visit compliance in third trimester pregnant women. Quantitative research with a cross sectional approach and purposive sampling technique on 30 third trimester pregnant women, in October-November 2020. Using a questionnaire and data analysis using Chi-Square. Characteristics of respondents aged 20-35 years (93.3%), primigravida (56.7%), secondary education (60%), less knowledgeable (60%), obedient to antenatal visits (76.7%). The p-value=1,000. There is no significant relationship between the knowledge of third trimester pregnant women about signs of bleeding during pregnancy and compliance with antenatal visits at the Cipayung District Health Center, East Jakarta. Nurses have a duty to provide counseling regarding the compliance of third trimester pregnant women in antenatal visits to prevent the risk of bleeding.